(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
The aim of this study is to study the effect of Yashtimadhu churna mukhalepa as a Varnya (Complexion .The main objectives of the study are to study the effect of Yashtimadhu churna mukhalepa to increase fairness & to prevent other skin disorder like rash, acne, etc In this study we have taken Yashtimadhu churna & Madhu which are identified, authentified & standerdized from Certified laboratory. The selected subjects were divided in two groups. In group A Yashtimadhu churna with honey Mukhalepa (Paste) was given & in Group B Yashtimadhu churna with water Mukhalepa was given. Duration – 45 days This is Two Arm, Randomized comparative, open label, prospective clinical study. We have taken Fitzpatrick scaleas a objective assessment criteria. for the statistical analysis Wilcoxon Signed Rank Test for group A & Group B, comparison between Group A & Group B were tested using Mann Whitteny Test. The results were statistically analysed for better interpretation. In comparison of both the groups no significant difference seen in objective parameter but there was significant results improving skin texture found in group A as compared to group B. Also there was significant improvement in complexion after 45 days of application in both the groups.